Health Risk Assessment of AIMS Employees: Basis towards the Development of an Enhanced Wellness Program - Garibay, Marianne; Amonceda, Angelina (Future Science / FSH-PH Publications, 2023)
This study explored the relationship between medical and mental health status among Asian Institute of Maritime Studies (AIMS) employees, employing statistical analyses such as Pearson correlation coefficients and t-tests. The results indicated a lack of significant correlation between medical and mental health status, suggesting no strong evidence supporting a relationship. Gender differences in health concerns were evident, with female employees reporting significantly higher levels of mental health concerns compared to their male counterparts. However, no substantial gender-based disparity was found in medical health concerns. Civil status also emerged as a significant factor, with single employees exhibiting notably higher mental health concerns than their married counterparts. Medical history included high blood pressure, stomach pain/ulcer, and nose/throat issues, with some reporting alcohol and smoking history. A minority were currently on medications for blood pressure, cholesterol, and diabetes. The study highlights the need to address mental health, especially among female employees, and implement strategies to reduce stress and enhance well-being in the workplace at AIMS. In light of these findings, the study recommended targeted programs addressing mental health concerns among AIMS employees, emphasizing accessibility to counseling services and collaborative efforts with the Human Resource Management Office (HRMO). Additionally, initiatives promoting digital literacy, fitness programs, and team-building activities were suggested. Recognizing the importance of early intervention, the study encouraged employees to consult with healthcare professionals for appropriate diagnosis and treatment measures for managing depression.